A higher spectral range of beetle bioluminescence with infraluciferin - Jathoul, Amit P.; Branchini, Bruce R.; Anderson, James C.; Murray, James A. H. (Frontiers in Bioengineering and Biotechnology, 2022)
Coleopteran bioluminescence is unique in that beetle luciferases emit colors ranging between green (ca.550 nm) and red (ca.600 nm), including intermediate colors such as yellow and orange, allowing up to 3 simultaneous parameters to be resolved in vitro with natural luciferin (D-LH2). Here, we report a more than doubling of the maximum bioluminescence wavelength range using a single synthetic substrate, infraluciferin (iLH2). We report that different luciferases can emit colors ranging from visible green to near-infrared (nIR) with iLH2, including in human cells. iLH2 was designed for dual color far-red to nIR bioluminescence imaging (BLI) in small animals and has been utilized in different mouse models of cancer (including a metastatic hepatic model showing detailed hepatic morphology) and for robust dual parameter imaging in vivo (including in systemic hematological models). Here, we report the properties of different enzymes with iLH2: Lampyrid wild-type (WT) Photinus pyralis (Ppy) firefly luciferase, Ppy-based derivatives previously engineered to be thermostable with D-LH2, and also color-shifted Elaterid-based enzymes: blue-shifted Pyrearinus termitilluminans derivative Eluc (reported D-LH2 λmax = 538 nm) and red-shifted Pyrophorus plagiopthalamus derivative click beetle red (CBR) luciferase (D-LH2 λmax = 618 nm). As purified enzyme, in bacteria or in human cells, Eluc emitted green light (λmax = 536 nm) with DL-iLH2 whereas Ppy Fluc (λmax = 689 nm), x2 Fluc (λmax = 704 nm), x5 Fluc (λmax = 694 nm), x11 Fluc (λmax = 694 nm) and CBR (λmax = 721 nm) produced far-red to nIR peak wavelengths. Therefore, with iLH2, enzyme λmaxes can be separated by ca.185nm, giving almost non-overlapping spectra. This is the first report of single-substrate bioluminescence color emission ranging from visible green to nIR in cells and may help shed light on the color tuning mechanism of beetle luciferases. We also report on the reason for the improvement in activity of x11 Fluc with iLH2 and engineer an improved infraluciferase (iluc) based on this mutant.